Respiratory epithelium: Place of entry and / or defense against SARS-CoV-2 virus - Leštarević Snežana (Medicinski fakultet Priština, Društvo lekara Kosova i Metohije Srpskog lekarskog društva, 2021)
Coronavirus Disease (COVID-19) is caused by the RNA virus SARS-CoV-2. The primary receptor for the virus is most likely Angiotensin-converting enzyme 2 (ACE2), and the virus enters the body by infecting epithelial cells of the respiratory tract. Through the activation of Toll Like Receptors (TLRs), epithelial cells begin to synthesize various biologically active molecules. The pathophysiology of the COVID 19 is primarily attributed to the hyperactivation of host's immune system due to direct damage to the cells, with consequent release of proinflammatory substances, but also due to the activation of the innate immune response through the activation of alveolar macrophages and dendrite cells (DC). A strong proinflammatory reaction causes damage to alveolar epithelial cells and vascular endothelium. Respiratory epithelial cells, alveolar macrophages and DC are likely to be the most important cells involved in the innate immune response to the virus, since prolonged and excessive SARS-CoV-2-induced activation of these cells leads to the secretion of cytokines and chemokines that massively attract leukocytes and monocytes to the lungs and cause lung damage.